Phosphoserine Aminotransferase1 Is Part of the Phosphorylated Pathways for Serine Biosynthesis and Essential for Light and Sugar-Dependent Growth Promotion - Wulfert, Sabine; Krueger, Stephan (Frontiers in Plant Science, 2018)
The phosphorylated pathway of serine biosynthesis represents an important pathway in plants. The pathway consist of three reactions catalyzed by the phosphoglycerate dehydrogenase, the phosphoserine aminotransferase and the phosphoserine phosphatase, and the genes encoding for all enzymes of the pathway have been identified. Previously, the importance of the phosphoglycerate dehydrogenase and phosphoserine phosphatase for plant metabolism and development has been shown, but due to the lack of T-DNA insertion mutants, a physiological characterization of the phosphoserine aminotransferase is still missing. Hence, we generated silencing lines specifically down-regulated in the expression of the major PSAT1 gene. The morphological characterization of the obtained PSAT1-silenced lines revealed a strong inhibition of shoot and root growth. In addition, these lines are hypersensitive to the inhibition of the photorespiratory serine biosynthesis, when growing the plants at elevated CO2. Metabolic analysis of PSAT1-silenced lines, showed a strong accumulation of certain amino acids, most likely due to an enhanced ammonium assimilation. Furthermore, phenotypic analysis under low and high-light conditions and in the presence of sucrose revealed, that the phosphorylated pathway of serine biosynthesis is essential for light and sugar-dependent growth promotion in plants.